On the Solution of Volterra Integro-differential Equations using a Modified Adomian Decomposition Method - Kabiru Oyeleye Kareem; Morufu Olayiwola; Oladapo Asimiyu; Yunus Akeem; Kamilu Adedokun; Ismail Alaje (Jambura Journal of Mathematics, 2023)
The Adomian decomposition method’s effectiveness has been demonstrated in recent research, the process requires several iterations and can be time-consuming. By breaking down the source term function into series, the current work introduced a new decomposition approach to the Adomian decomposition method. As compared to the conventional Adomian decomposition approach, the newly devised method hastens the convergence of the solution. Numerical experiments were provided to show the superiority qualities.